Sosialisasi Hukum Tentang Kdrt Bersama Ibu-Ibu Pkk Rt 16 Rw 05 Kelurahan Sawah Lebar - Intan Permata Sari; Riki Sumansyah; Devri Aryansyah; Artika Sari Devi; Bimo Restu Putra; Herlin Herlin; Devi Sartika; Lydia Margaretha (Jurnal Karya Nyata Pengabdian, 2026)
Domestic violence (DV) is a social problem that persists frequently in society, particularly against women and children. Lack of understanding of the law and protection of victims of domestic violence leads to many cases going unreported and continuing to recur. This DV legal outreach activity aimed to increase the understanding of the Family Welfare Movement (PKK) women in RT 16 RW 05, Sawah Lebar Village, regarding the forms of domestic violence, their impacts, and legal protection mechanisms under Law Number 23 of 2004 concerning the Elimination of Domestic Violence. The implementation method included counseling, interactive discussions, and a question-and-answer session. The results demonstrated increased knowledge and awareness among participants regarding the importance of preventing and reporting domestic violence to create harmonious and safe families.